Wireless Android-Based Control of Plastic Crane Roll Control Prototype - Akhmad Solikin; Yulfi Ainun Al Farizi; Yanantra Budi Pramana (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2022)
Abstract - Overhead crane is a lifting tool used by almost all industries, ports, warehouses, workshops, and others. In general, the overhead crane control system is less effective and efficient because the operator still follows the direction of the crane's speed. In this case, problems often occur because the pendant switch which functions as a controller still uses a cable as a connector to the overhead crane panel. Various problems that often occur include cables breaking frequently due to being hit by a load lifted by the hoist, operators having difficulty setting a safe distance because they are limited by the length of the pendant switch cable. Based on the background of the problem, a control system is made which is expected to be able to control the overhead crane effectively and efficiently without using a cable as a connector but using an android smartphone. Control with an android smartphone using an android application with a wifi connection and an arduino uno R3 microcontroller. Based on the test results on this control system, device control can be controlled at a maximum distance of ± 100 meters as long as the device is still within wifi range. The control system can function optimally and the application can be installed on Android OS 4.0 (Jelly Bean) smartphones. Therefore, the use of a cable can be replaced with a wifi connection system to reduce friction with the cable and so that the operator can maintain a safe distance from the load to be moved because it is no longer limited by the length of the cable.